PROFIL PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IX SMP PADA MATERI LINGKARAN - Fujiwara T. M Kaili; Agung Wicaksono (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
The purpose of this study was to describe the mathematics problem solving profile of grade IX junior high school students on circle material. Disclosure of the problem-solving profile is based on the problem-solving steps of the pattern, namely: (a) understanding the problem; (b) conducting the test by giving questions with circle material and (c) checking the results of the work that has been made. This research uses qualitative research with a qualitative descriptive approach. This research was conducted online with the subject of grade IX students of SMP Negeri 13 Palu in 2020. The process of determining the subject in this study was by taking students with low, medium and high abilities. The techniques used to obtain data in this study were written tests, in-depth interview techniques and observation techniques. The results of the study state that (1) the S1 comprehension profile is to repeat the reading of the questions repeatedly in order to understand what is being asked in the questions and to help recall the formula. (2) Profile of S2 understanding by repeating the reading of the questions less than S1 so that you can understand what is being asked in the question and try to remember the formula for solving the problem again. (3) The S3 comprehension profile is reading the questions at least from S1 and S2 until you understand what is being asked in the questions. (4) In solving the questions, S1 does the first question then the second problem. When answering questions, S1 answers all questions without asking many questions so that they are more concentrated and focused in order to solve the questions given by the researcher according to their previous understanding. (5) In solving the problem, working on the first question then the second question and when answering the question, S2 answers by asking a little to make sure he is. (6) In solving the questions, S3 works on the first problem then the second problem. (7) Profile checking back answers, S1 re-checks repeatedly to convince himself with the answer. (8) Profile of checking back answers, S2 re-checks by reading the questions again and then the answers and convincing himself. (9) Re-checking profile answers, S3 performs re-examination by repeating reading and understanding the questions then the formula and convincing themselves and the researcher with the answers.